Serum Matrix Metalloproteinase-9, Tissue Inhibitor of Metalloproteinase-1 and Matrix Metalloproteinase-9/ Neutrophil Gelatinase-associated Lipocalin Complex Levels in Patients With Early-stage Diabetic Nephropathy (Iranian Journal of Kidney Diseases, 2018)
Introduction. This study was aimed to investigate the efficacy of matrix metalloproteinase-9 (MMP-9), tissue inhibitor of metalloproteinase-1 (TIMP-1), and the neutrophil gelatinase-associated lipocalin (NGAL)-bound form of MMP-9 (MMP-9/NGAL complex) markers in the determination of early nephropathy in patients with type 2 diabetes mellitus. Materials and Methods. Twenty-five type 2 diabetic patients with normoalbuminuria, 27 type 2 diabetic patients with microalbuminuria, and 23 healthy controls were recruited. Serum levels of MMP-9, TIMP-1, and MMP9/NGAL complex were measured in all participants. Results. The MMP-9 level and MMP-9/TIMP-1 ratio were higher in patients with microalbuminuria when compared to the controls, while TIMP-1 level was lower (P = .005, P = .006, and P = .02, respectively). The MMP-9 level and MMP-9/TIMP-1 ratio were significantly higher in the patients with normoalbuminuria when compared to the controls (P = .005 and P = .02, respectively). In the normoalbuminuric patients, MMP-9 levels were negatively correlated with estimated GFR (r = -0.553, P = .008) and positively correlated with glucose (r = 0.449, P = .04), creatinine (r = 0.454, P = .03), and MMP9/NGAL complex (r = 0.575, P = .005). In the microalbuminuric patients, MMP-9 levels were positively correlated with total cholesterol (r = 0.430, P = .03), and MMP9/NGAL complex (r = 0.650, P = .001). Conclusions. The levels of MMP-9, TIMP-1, and MMP9/NGAL complex were similar in microalbuminuric and normoalbuminuric patients with type 2 diabetes mellitus. However, there was a significant MMP-9/TIMP-1 imbalance in both groups which may reflect impaired extracellular matrix homeostasis.